(untitled) (Revista Electrónica Calidad en la Educación Superior, 2017)
Se realizó una investigación descriptiva con el objetivo de evaluar la calidad de un curso virtual de formación docente, usando el Modelo de Evaluación de Cursos Virtuales de Formación Continua del Instituto Latinoamericano de Calidad en Educación a Distancia (CALED). Mediante la aplicación de una lista de verificación y cuatro cuestionarios, se analizaron 72 indicadores de las áreas: calidad tecnológica, formación, diseño instruccional y servicios y soporte. Los resultados indican cumplimiento parcial de los estándares de calidad. Las áreas de mayor cumplimiento en orden decreciente fueron: formación, diseño instruccional y servicios y soporte. En el área de calidad tecnológica se cumple con la mayoría de los requerimientos y en algunos casos no se encontraron registros requeridos como evidencias de la evaluación. QUALITY OF AN E-LEARNING VIRTUAL COURSE IN HEALTH SCIENCES Abstract A descriptive study was conducted in order to evaluate the quality of a virtual course on teacher training, using the Evaluation Model of the Virtual Continuous Training Courses of the Latin American Institute for Quality in Distance Education (CALED, in Spanish). By applying a checklist and four questionnaires, there were analyzed 72 indicators for the following areas: Technological quality, training, instructional design and services and support. The results indicate a partial accomplishment of the quality standards. The areas of greatest fulfillment in descending order were training, instructional design and services and support. In the area of technological quality most of the requirements were met, but in many cases, no required records were found as evidence at the time of the assessment. Keywords: Distance education; educational evaluation; educational quality; teacher education.